2019
DOI: 10.1186/s40249-019-0560-6
|View full text |Cite
|
Sign up to set email alerts
|

Infection against infection: parasite antagonism against parasites, viruses and bacteria

Abstract: Background Infectious diseases encompass a large spectrum of diseases that threaten human health, and coinfection is of particular importance because pathogen species can interact within the host. Currently, the antagonistic relationship between different pathogens during concurrent coinfections is defined as one in which one pathogen either manages to inhibit the invasion, development and reproduction of the other pathogen or biologically modulates the vector density. In this review, we provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 133 publications
(189 reference statements)
0
57
0
Order By: Relevance
“…In addition, both HK and Kit W / Wv mice have reduced basophil numbers. Basophils have been shown in several studies to become activated in an IgE-dependent and -independent manner to various fungi (40)(41)(42). Therefore, a contribution of basophils cannot be excluded and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, both HK and Kit W / Wv mice have reduced basophil numbers. Basophils have been shown in several studies to become activated in an IgE-dependent and -independent manner to various fungi (40)(41)(42). Therefore, a contribution of basophils cannot be excluded and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is being shown that vaccine against one pathogen can provide a long lasting immunity against another pathogen [5]. In this antagonistic phenomenon, pathogen of certain species can inhibit the infection by another one through inhibiting the invasion, survival and/or reproduction of another pathogen [9].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is being shown that vaccine against one pathogen can provide a long lasting immunity against another pathogen [5]. In this antagonistic phenomenon, pathogen of certain species can inhibit the infection by another one through inhibiting the invasion, survival and/or reproduction of another pathogen [9]. Different parasites are been reported to reduce the severity of viral infections, one of such example comes from Giardia which can reduce the severity and infection of rotavirus if concurrent infection takes place [10].…”
Section: Discussionmentioning
confidence: 99%
“…Such parasite exposure induced stunting of severity of viral infections is well known, for example, Giardia lamblia induced modulation of rotaviral infection, 25 and protection against Chikungunya virus by infection with Plasmodium spp 26,27 . Various immune mechanisms for such cross‐protection are hypothesized, like immunomodulation, suppression of dendritic cell responses, activation of basophils and phagocytic macrophages and modulation the complement system, among others 28 …”
Section: Discussionmentioning
confidence: 99%